Bioethics in Cultural Contexts: Reflections on Methods and Finitude - Rehmann-Sutter, Christoph (International Library of Ethics, Law, and the New Medicine, 2006)
"This book discusses a range of methodological issues for an interdisciplinary bioethics. How can bioethics be an enterprise that does not only isolate issues and moral reasons but also (re)contextualises them? What are the strengths and weaknesses of different traditional and innovative modes of ethical work in terms of these tasks? By introducing the term ""finitude"" in the sense of limits of human existence, limits of human knowledge and knowledge capacity, a difference was set in the cultural apprehension of medicine. Is medicine aimed at overcoming our existential limits: to fight diseases and prolong life? Finitude reintroduces the existential and cultural basis on which every medicine (limits-sensitive or off-limits medicine) depends, but it concerns also ethical judgment. An apprehension of the limitations of different ethical approaches to biomedicine, however, could strengthen the collaborative effort of an interdisciplinary bioethics that embraces also cultural studies and social sciences."